How to make deregulation work. - Sweet, W. (IEEE spectrum)
Every regulated industry manifests the same rules, while each deregulated industry is unruly or even dysfunctional in ways unique to it. Figuring out how to fix each one's problems is in its own right a huge technological challenge-technological in the economist's sense of referring to all aspects of business organization. Alfred Kahn, the father of airline deregulation, continues to publish frequently on all aspects of regulation and to give testimony when his views are solicited, which they frequently are. In the interview given in this article, Kahn expresses skepticism about introducing consumer choice in electricity, mounts a robust defense of airline deregulation, and expresses some optimism about the prospects of making local telephone systems more competitive